Characterizing Risk Behaviour of Maize Farmers using the Experimental Gambling Approach: An Empirical Study in Ghana - Samuel Kwesi Ndzebah Dadzie; William Larbi; William Ghartey (Universitas Sebelas Maret, 2022)
Along the maize value chain in Ghana are a wide range of risks that confront actors; the risk chain actors' face include production and marketing risks. Accordingly, risk management, which has become an integral part of maize value chain activities, is challenged with several factors, some of which are economic, institutional, social and behavioral factors. This study posits that risk preferences/behavior of farm decision-makers in the maize value chain have empirical importance for economic and policy analysis. Thus, an experimental gambling approach was used to elicit the risk aversion behavior of respondents (farmers). Here, the respondents' risk aversion behavior over varying game levels was investigated. The multinomial logit model was used to investigate endogenous and exogenous factors explaining the risk behavior. The data were obtained by interviewing 220 maize farmers who were sampled with a two-stage sampling procedure. This study revealed that most of the farmers in the study area exhibited risk aversion behavior. About 33% of farmers showed extreme risk aversion behavior at the games’ lowest level and increased to 45% as the game level rose. It was also found that sex, age, level of formal education, access to credit, access to the storage facility, household size, farm size and the number of extension visits to the farm significantly explained the risk aversion behavior the maize farmers exhibited. Because farmers are risk-averse and become more risk-averse as stakes become high, any farm innovations to be introduced to them must be implemented gradually, especially with the low-income farmers. It is also critical to make risk mitigation 'handles' available to farmers so that they can rely on them during times of risk.